Mauritius : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2008)
A detailed assessment report on Anti-Money Laundering and Combating the Financing of Terrorism for Mauritius is discussed. Mauritius is well placed to capitalize on its national strategy to diversify its economy into global financial services by taking advantage of its linkages with both African and long-standing arrangements with the larger Asian economies. Additionally, Mauritius intends to offer new products in Islamic financial services and wealth management. The investigative and prosecutorial authorities have the necessary powers to execute their respective functions.